As manifestações do cômico nas Saturae de Juvenal - Carmo, Rafael Cavalcanti do (2014)
Juvenal, a satirical poet of the Roman Empire whose poetry was written between the second and third decades of the second century A.D., has indignatio as his most remarkable form of poetic expression. Such choice conditioned the rise of controversial questions about the modern reception of his poetry, manifested in readings that, most of the time, isolated this poetry from de comic aspect related to satire. The goal of this dissertation is, making the link between satire and comic, discuss what of laughable exists in Juvenal’s poems. The main object of our investigation, in this direction, has been the very construction of the satirist’s poetic voice, an ambiguous process which, we believe, is apt to demonstrate the presence of humor in the poet’s work.